Knowledge and attitude of final year nursing students towards pediatric pain at School Of Health Sciences, Universiti Sains Malaysia (USM) - Razak, Siti Shaqwanah Abd (Universiti Sains Malaysia, 2015)
Pediatric pain is a challenging issue among healthcare workers; this includes nursing students as they will become nurses in future. Students nurses' knowledge and attitude towards pediatric pain seem to affect their pain assessment and management in pediatric during clinical practice. A cross sectional, descriptive statistic study was carried out to assess the knowledge and attitude of student nurses towards pediatric pain. Total of 100 final year nursing students in School of Health Sciences, USM completed the questionnaires by convenience sampling technique that the fits inclusion criteria. Data was statistically analyzed using the software package SPSS version 22. Statistical significance was considered at p value <0.05. Among 100 respondents (n=100), 74 (74.0%) respondents showed that they had moderate level of knowledge and 49 (49.0%) of the respondents had positive attitude. Independent t-test showed a significant association between clinical experience at pediatric unit with knowledge p<0.05 and attitude score p<0.05. Besides that, independent t-test also showed a significant association between level of education with knowledge score p<0.05 and attitude score p<0.05. In conclusion, this research finding indicated there were associations between clinical experiences in pediatric unit as well as level of education with knowledge and attitude among final year nursing students in USM.